2006
DOI: 10.1007/s00442-006-0526-9
|View full text |Cite
|
Sign up to set email alerts
|

Highly predictable photosynthetic production in natural macroalgal communities from incoming and absorbed light

Abstract: Photosynthesis-irradiance relationships of macroalgal communities and thalli of dominant species in shallow coastal Danish waters were measured over a full year to test how well community production can be predicted from environmental (incident irradiance and temperature) and community variables (canopy absorptance, species number and thallus metabolism). Detached thalli of dominant species performed optimally at different times of the year, but showed no general seasonal changes in photosynthetic features. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 33 publications
4
65
2
1
Order By: Relevance
“…The live assay allows for quantification of the overall palatability of F. vesiculosus, which may depend upon chemical as well as structural traits. However, the possibility that F. vesiculosus changes its palatability (Middelboe et al 2006). Corresponding with these data, respiration of F. vesiculosus from Kiel was in the present study compensated at 17 碌E m -2 s -1 in early March, while positive growth in summer was impossible when the mean daily PAR was < 35 碌E m -2 s -1 .…”
Section: Discussionsupporting
confidence: 83%
“…The live assay allows for quantification of the overall palatability of F. vesiculosus, which may depend upon chemical as well as structural traits. However, the possibility that F. vesiculosus changes its palatability (Middelboe et al 2006). Corresponding with these data, respiration of F. vesiculosus from Kiel was in the present study compensated at 17 碌E m -2 s -1 in early March, while positive growth in summer was impossible when the mean daily PAR was < 35 碌E m -2 s -1 .…”
Section: Discussionsupporting
confidence: 83%
“…Spring and autumn changes in pH were significantly related to changes in irradiance but not to change in temperature, suggesting that temperature plays a lesser role than irradiance in the seasonal differences in community photosynthetic production. This is in agreement with recent studies on community photosynthesis which have shown that the photosynthetic characteristics of communities vary but little during the year and that irradiance is the main factor determining photosynthetic production in natural macroalgal communities (Middelboe et al 2006). pH and diurnal variability were highest in the shallowest waters and decreased with increasing water depth.…”
Section: Level and Variability Of Ph In Shallow-water Habitatssupporting
confidence: 92%
“…One site was a wave-exposed boulder reef in Aalsgaarde, on the northern coast of Zealand, Denmark, with relatively steep bottom topography. The boulder reef was densely covered with species-rich macroalgal communities dominated by Fucus species (Middelboe et al 2006). The other site was a sheltered, shallow-water area in Kildebakkerne in the estuary Roskilde Fjord, Denmark.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Canopy openness and tree density are structural components that influence the light and temperature environment of the forest floor, and so are important forest structure characteristics contributing to the dynamics of forest patches (Pickett & White 1985). Canopy structure was an important predictor of benthic primary production because of the relationship of canopy height to photosynthesis and irradiance in macroalgal communities of shallow coastal water (Middelboe et al 2006). We found differences in canopy openness among the various mangrove management types in our study; canopy openness was lowest in RIM and higher in control and breached-RIM swamps (Table 3).…”
Section: Forest Structural Complexitymentioning
confidence: 59%